Hubungan Kemampuan Berpikir Komputasional dengan Hasil Belajar Kognitif Materi Pewarisan Sifat Makhluk Hidup Berdasarkan Hukum Mendel - Suryanda, Ade; Dewahrani, Yulilina Retno; Afifah, Siti Nur (Biosfer: Jurnal Pendidikan Biologi, 2024)
Biology learning in the 21st century requires students to understand complex genetics concepts, particularly the inheritance of traits in living organisms based on Mendel's laws. Computational thinking skills are essential for helping students systematically analyze and solve these intricate genetic patterns. This study aims to analyze the relationship between computational thinking skills and cognitive learning outcomes on the material of the inheritance of living creatures’ traits based on Mendel’s law. The research method used is descriptive with a correlational study. This study employed a descriptive correlational research method, conducted at SMAI PB Soedirman with a sample of 87 twelfth-grade science students from 203 students with an average age of 17-18 years and a balanced proportion of male and female selected through simple random sampling. The instruments used included questionnaires to measure computational thinking skills and tests to assess cognitive learning outcomes in genetics. Data analysis involved descriptive statistics to summarize the data and correlational analysis using Pearson’s Product-Moment to explore the relationship between variables. The tests that have been carried out show that there is a significant positive and linear relationship between computational thinking skills and cognitive learning outcomes of genetic trait inheritance based on Mendel’s law. The strength level of the relationship between the two variables is moderate.